(untitled) (Gadau Journal of Pure and Allied Sciences, 2024)
Fruits and vegetables are important components of human diet that could be contaminated by different kinds of microorganisms. Microbial contamination may occur during any steps of transportation or processing from farm-to-table due to many environmental, animal, and human sources as well as technological applications. This study aimed at assessing the bacteriological contaminants of fruits and vegetables sold in Gombe metropolitan. A total of 30 fruits and vegetables samples were purchased from different vendors and transported to the Microbiology Laboratory for processing. Ten-fold serial dilution was performed on each sample and aliquots of 10-1-10-3 dilutions were inoculated on Nutrient Agar and MacConkey Agar plates using pour-plate technique. The plates were incubated for 24 hours at 37oC and then observed for aerobic mesophilic and faecal coliform counts. The bacterial loads of the samples ranged from 3.7x104 to 2.7x105 and 2.9x104 to 8.7x104 for total mesophilic and faecal coliform counts, respectively. Subsequently, a total of eight bacteria were isolated and identified as Escherichia coli, Salmonella spp., Klebsiella spp., Enterobacter spp., Pseudomonas spp., Staphylococcus aureus, Bacillus cereus, and Shigella spp. In conclusion, the fruits and vegetables were found to be contaminated with different bacterial species of public health concern.